The proposed trigger-less TBit/s readout for the Mu3e experiment - Bachmann, Sebastian; Berger, Niklaus; Blondel, A.; Bravar, S.; Buniatyan, Armen; Dissertori, G.; Eckert, Patrick; Fischer, Peter; Grab, C.; Gredig, R.; Hildebrandt, M.; Kettle, P.-R.; et al. (Journal of Instrumentation, 2014)
The Mu3e experiment searches for charged lepton flavor violation in the rare decay μ→eee with a projected sensitivity of 10−16. A precise measurement of the decay product momenta, decay vertex and time is necessary for background suppression at rates of 109 muons/s. This can be achieved by combining an ultra-lightweight pixel tracker based on HV-MAPS with two timing systems. The trigger-less readout of the detector with three stages of FPGA-boards over multi GBit/s optical links into a GPU filter farm is presented. In this scheme data from all sub-detectors is merged and distributed in time slices to the filter farm.
Gesehen am 02.11.2020